Antioxidant and cytotoxic activities of Calophyllum rubiginosum - Alkhamaiseh, Suhaib Ibrahim; Bakhtiar, M. Taher; Ahmad, Farediah; Arief Ichwan, Solachuddin Jauhari; Darnis, Deny Susanti (Advanced Research Journals, 2011)
Clusiaceae / Guttiferae an evergreen shrubs or trees, it is considered as a family of 27 genera and 1090 species. Calophyllum rubiginosum one of these species and belongs to this family. In Malaysia they use it as folk remedies, where they believe its’ activity. Problem: Evaluation of antioxidant and cytotoxic activities of three fractions. n-hexane, dichloromethane (DCM) and methanol (MeOH) of Calophyllum rubiginosum species. Approach: The three main fractions were tested to find out the antioxidant capacity using three different methods, DPPH radical scavenging, reducing power and chelating iron ions. The fractions were tested against lung cancer A-549 cell line to assess the anti-proliferation activity. Results: The MeOH fraction showed no effect against lung cancer cell line but achieved a significant result in antioxidant testing. The DCM and n-hexane fractions considered as moderate antioxidant agent, they showed a significant result against lung cancer cell line. Non and semi polar fractions were able to inhibit the proliferation of A-549 cell line at low concentration. The results were statistically significant (P< 0.05). Conclusions: C. rubiginosum fractions have showed significant activity. DCM and n-hexane fractions proved to be effective against A-549 lung cancer cell line, where they were able to disturb the cell proliferation. These results can benefit the local community, and to guide how to use this plant.